Spatial Planning and Remote Teamwork - Voigt, Andreas; Linzer, Helena (International Journal of Virtual Reality, 1997)
The following contribution describes work in progress within the context of the focal field of research and development remote teamwork (RT) of Vienna University of Technology (Dept. of Local Planning - IFOR), which is carried out in cooperation with the Institute for Spatial Interaction and Simulation (IRIS-ISIS), Vienna, exchanging experience with the Research Institute for Symbolic Computation (RISC Linz-Hagenberg). Research work is aimed at the elaboration of suitable collaborative remote working structures for research and project transactions, including study projects, within the context of spatial planning on the basis of ATM (Asynchronous Transfer Mode: a technology of broad band telecommunications). The generation and manipulation of digital spatial models and their virtual transportation within large spatial distances represent main objectives. The current subjects in urban and regional planning and in architecture act as test projects to be defined in the course of the research project in their contents and spatial context and to be represented as digital spatial working models.